Break clauses - Warwick, Mark; Trompeter, Nicholas ([London, England] : Hart Publishing, 2021)
"This is the only book to deal exclusively with the important topic of break clauses, which affect a significant proportion of all landlord and tenant relationships. The book provides a comprehensive and authoritative survey of the law relating to the drafting and operation of break clauses. It covers over 500 cases relevant to the topic. The book also considers the areas of the law that interrelate with break clauses, including contractual construction, assignment, estoppel, mistake and professional negligence. Previous editions of Break Clauses have been referred to as ?scholarly and practical? (Sir Kim Lewison) and ?excellent and much needed? (Lord Neuberger). This new edition includes the most recent and relevant judgments that have had an important impact on the law affecting break clauses. There are two new chapters: one on the interrelationship between break clauses and compulsory purchase (of particular relevance in light of large-scale projects such as HS2 and Crossrail) and one on the interrelationship between break clauses and rent review. The third edition covers new legal developments, including the new Electronic Communications Code and its impact on break clauses."--
Foreword to the Second Edition -- Foreword to the First Edition -- 1. The Nature of a Break Clause -- 2. Formalities and Registration -- 3. Assignment -- 4. Who May Exercise the Break Clause -- 5. The Form and Content of the Break Notice -- 6. The Time for Exercise of the Break Clause and Service of the Break Notice -- 7. The Method of Service of the Break Notice -- 8. On Whom the Break Notice Should Be Served -- 9. Conditions in a Break Clause: General Principles -- 10. Particular Conditions in a Tenant's Break Clause -- 11. The Recovery of 'Overpaid' Rent and Other Sums -- 12. Redevelopment Break Clauses -- 13. Invalid Break Notices: Waiver, Estoppel and Withdrawal -- 14. The Effect of Exercising a Break Clause -- 15. Break Clauses and Compulsory Purchase -- 16. Break Clauses and Rent Review -- 17. Professional Liability -- 18. Business Tenancies -- 19. Residential Tenancies -- 20. Agricultural Tenancies -- 21. Drafting Break Clauses -- 22. Practical Advice When Exercising a Break Clause -- Appendix 1: Break Clause for the Landlord - On One or More Specified Dates -- Appendix 2: Break Clause for the Landlord - Incorporating a Rolling Break -- Appendix 3: Break Clause for the Tenant - On One or More Specified Dates -- Appendix 4: Break Clause for the Tenant - Incorporating a Rolling Break -- Appendix 5: Particulars of Claim - Landlord's Claim for Declaration etc. -- Appendix 6: Defence and Counterclaim - In Response to Landlord's Claim for Declaration etc. -- Index
Includes index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Leases -- England; Leases -- Wales; Landlord and tenant -- England; Landlord & tenant law,England,Wales; Electronic books